2018
DOI: 10.1007/s13187-018-1342-8
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Awareness and Behavioral Determinants Associated with Cancer Prevention—a Quantitative Study Among Young Adults in Rural Settings

Abstract: Although college is a crucial time to establish healthy behaviors for cancer prevention, little is known about cancer awareness and behaviors among US college students in less economically developed, rural areas. The purpose of this study was to examine college students' cancer-preventative knowledge and health behaviors. This cross-sectional study was conducted at a large southeastern university in the USA, on a convenience sample of students attending a campus-wide health education class. Data were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 22 publications
1
8
2
1
Order By: Relevance
“…Smoking enjoyed worldwide high publicity as a cancer risk factor and it is interesting that adolescents were better at recognizing this risk factor than adults. However, except for smoking as a risk factor, general awareness rates were poor in this study compared to other studies, which showed proportions of 60-88% recognizing smoking, 21-50% recognizing 'eating less than five portions of fruit and vegetables a day' and around 30% recognizing the importance of exercise, compared to 76.7, 17.8 and 25.0% respectively in this study [18,22,29,41]. This discrepancy could be due to the fact that a number of awareness campaigns have been done on factors such as smoking, exercise and healthy diet in the localities of these other studies [27,40,[42][43][44].…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Smoking enjoyed worldwide high publicity as a cancer risk factor and it is interesting that adolescents were better at recognizing this risk factor than adults. However, except for smoking as a risk factor, general awareness rates were poor in this study compared to other studies, which showed proportions of 60-88% recognizing smoking, 21-50% recognizing 'eating less than five portions of fruit and vegetables a day' and around 30% recognizing the importance of exercise, compared to 76.7, 17.8 and 25.0% respectively in this study [18,22,29,41]. This discrepancy could be due to the fact that a number of awareness campaigns have been done on factors such as smoking, exercise and healthy diet in the localities of these other studies [27,40,[42][43][44].…”
Section: Discussioncontrasting
confidence: 92%
“…The school curriculum content might be reflected in the fact that more adolescents than adults knew that 'smoking' and 'eating less than five portions of fruit and vegetables a day' were risk factors for cancer, both of which are facts actually 'taught' at school. In most studies 'smoking' was the most commonly recognized risk factor [18,23,24,29,[39][40][41]. Smoking enjoyed worldwide high publicity as a cancer risk factor and it is interesting that adolescents were better at recognizing this risk factor than adults.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking enjoyed worldwide high publicity as a cancer risk factor and it is interesting that adolescents were better at recognizing this risk factor than adults. However, except for smoking as a risk factor, general awareness rates were poor in this study compared to other studies, which showed proportions of 60-88% recognizing smoking, 21-50% recognizing 'eating less than five portions of fruit and vegetables a day' and around 30% recognizing the importance of exercise, compared to 76.7%, 17.8% and 25.0% respectively in this study [18,23,30,43]. This discrepancy could be due to the fact that a number of awareness campaigns have been done on factors such as smoking, exercise and healthy diet in the localities of these other studies [28,42,[44][45][46].…”
Section: Discussioncontrasting
confidence: 93%
“…The school curriculum content might be reflected in the fact that more adolescents than adults knew that 'smoking' and 'eating less than five portions of fruit and vegetables a day' were risk factors for cancer, both of which are facts actually 'taught' at school. In most studies 'smoking' was the most commonly recognized risk factor [18,24,25,30,[41][42][43]. Smoking enjoyed worldwide high publicity as a cancer risk factor and it is interesting that adolescents were better at recognizing this risk factor than adults.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies demonstrate that adolescents are not well informed about cancer risk factors [4]. Current literature suggests that many adolescents and college students in the USA lack cancerpreventative knowledge and engage in cancer risk behaviors such as unhealthy diet, frequent alcohol consumption, and low physical activity [5,6]. In one study, only 49% of adolescents reported awareness of the human papillomavirus (HPV) vaccine and cervical cancer [7].…”
Section: Introductionmentioning
confidence: 99%